Participatory Management Approach for Online Learning in A Small Secondary School - Meeprom, Kasidit (An Online Journal of Education, 2022)
The objective of this research was to study the participatory management approach for online learning in a small secondary school under the Office of the Basic Education Commission, Ministry of Education. The population in this study consisted of school director, deputy director, school board, head of subject areas and teachers, students, representatives of the network of parents and supervising alumni, a total of 89 people. The research tool was a questionnaire, which was a 5-point rating scale. The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation and need analysis (PNIModified). The study results revealed that the participatory management approach with the highest priority needs in online learning was participation with the school in implementation and monitoring assessments (PNIModified = 0.068), especially in using learning materials and learning resources through various online channels such as Zoom, Google Meet, Microsoft Teams, Cloud Meeting to facilitate students who are ready to do so, such as mobile phones, notebook computers and Internet ( PNIModified = 0.080). And overall in online learning, the use of learning materials and learning resources through delivery of books, textbooks, exercises or worksheets prepared by the school to students through their parents (On-hand) in order to mitigate the cost of purchasing internet service and school supplies like mobile phones, notebooks, and computers was of the higghest priority needs (PNIModified = 0.069).